Pd-Catalyzed microwave-assisted synthesis of phosphonated 13α-estrones as potential OATP2B1, 17β-HSD1 and/or STS inhibitors - Jójárt, Rebeka; Pécsy, Szabolcs; Keglevich, György; Szécsi, Mihály; Rigó, Réka; Özvegy-Laczka, Csilla; Kecskeméti, Gábor; Mernyák, Erzsébet (Beilstein Journal of Organic Chemistry, 2018)
Novel 2- or 4-phosphonated 13α-estrone derivatives were synthesized via the Hirao reaction. Bromo regioisomers (2- or 4-) of 13α-estrone and its 3-benzyl or 3-methyl ether were reacted with diethyl phosphite or diphenylphosphine oxide using Pd(PPh3)4 as catalyst under microwave irradiation. The influence of the new compounds on the transport function of the organic anion transporting polypeptide OATP2B1 was investigated by measuring Cascade Blue uptake. Derivatives bearing a 3-benzyl ether function displayed substantial submicromolar OATP2B1 inhibitory activity. The inhibitory effects of the compounds on human placental steroid sulfatase (STS) and 17β-hydroxysteroid dehydrogenase type 1 isozyme (17β-HSD1) were investigated by in vitro radiosubstrate incubation methods. None of the test compounds inhibited the STS markedly. The structure–activity relationship evaluation revealed that 2-substituted 3-hydroxy derivatives are able to inhibit the 17β-HSD1 enzyme with submicromolar IC50 values. Dual OATP2B1 and 17β-HSD1 inhibitors have been identified.
Keywords: catalysis; enzyme; 13α-estrone; Hirao reaction; 17β-HSD1 inhibition; OATP2B1; STS

(untitled) - Miller, W. L.; Auchus, R. J. (Endocr. Rev., 2011)

(untitled) - Geyer, J.; Bakhaus, K.; Bernhardt, R.; Blaschka, C.; Dezhkam, Y.; Fietz, D.; Grosser, G.; Hartmann, K.; Hartmann, M. F.; Neunzig, J.; Papadopoulos, D.; Sánchez-Guijo, A.; et al. (J. Steroid Biochem. Mol. Biol., 2017)

(untitled) - Izumi, S.; Nozaki, Y.; Komori, T.; Maeda, K.; Takenaka, O.; Kusano, K.; Yoshimura, Y.; Kusuhara, H.; Sugiyama, Y. (Drug Metab. Dispos., 2013)

(untitled) - Roth, M.; Obaidat, A.; Hagenbuch, B. (Br. J. Pharmacol., 2012)

(untitled) - Hagenbuch, B.; Stieger, B. (Mol. Aspects Med., 2013)

(untitled) - Grube, M.; Köck, K.; Karner, S.; Reuther, S.; Ritter, C. A.; Jedlitschky, G.; Kroemer, H. K. (Mol. Pharmacol., 2006)

(untitled) - Grube, M.; Reuther, S.; Meyer zu Schwabedissen, H.; Köck, K.; Draber, K.; Ritter, C. A.; Fusch, C.; Jedlitschky, G.; Kroemer, H. K. (Drug Metab. Dispos., 2007)

(untitled) - Knauer, M. J.; Girdwood, A. J.; Kim, R. B.; Tirona, R. G. (Mol. Pharmacol., 2013)

(untitled) - Kovacsics, D.; Patik, I.; Özvegy-Laczka, C. (Expert Opin. Drug Metab. Toxicol., 2017)

(untitled) - Matsumoto, J.; Ariyoshi, N.; Sakakibara, M.; Nakanishi, T.; Okubo, Y.; Shiina, N.; Fujisaki, K.; Nagashima, T.; Nakatani, Y.; Tamai, I.; Yamada, H.; Takeda, H.; et al. (Drug Metab. Pharmacokinet., 2015)

(untitled) - Schweigmann, H.; Sánchez-Guijo, A.; Ugele, B.; Hartmann, K.; Hartmann, M. F.; Bergmann, M.; Pfarrer, C.; Döring, B.; Wudy, S. A.; Petzinger, E.; Geyer, J.; Grosser, G. (J. Steroid Biochem. Mol. Biol., 2014)

(untitled) - Ugele, B.; Bahn, A.; Rex-Haffner, M. (J. Steroid Biochem. Mol. Biol., 2008)

(untitled) - Marchais-Oberwinkler, S.; Henn, C.; Möller, G.; Klein, T.; Negri, M.; Oster, A.; Spadaro, A.; Werth, R.; Wetzel, M.; Xu, K.; Frotscher, M.; Hartmann, R. W.; et al. (J. Steroid Biochem. Mol. Biol., 2011)

(untitled) - Hong, Y.; Chen, S. (Mol. Cell. Endocrinol., 2011)

(untitled) - Buxhofer-Ausch, V.; Secky, L.; Wlcek, K.; Svoboda, M.; Kounnis, V.; Briasoulis, E.; Tzakos, A. G.; Jaeger, W.; Thalhammer, T. (J. Drug Delivery, 2013)

(untitled) - Arakawa, H.; Nakanishi, T.; Yanagihara, C.; Nishimoto, T.; Wakayama, T.; Mizokami, A.; Namiki, M.; Kawai, K.; Tamai, I. (Biochem. Pharmacol., 2012)

(untitled) - Yaremenko, F. G.; Khvat, A. V. (Mendeleev Commun., 1994)

(untitled) - Schönecker, B.; Lange, C.; Kötteritzsch, M.; Günther, W.; Weston, J.; Anders, E.; Görls, H. (J. Org. Chem., 2000)

(untitled) - Ayan, D.; Roy, J.; Maltais, R.; Poirier, D. (J. Steroid Biochem. Mol. Biol., 2011)

(untitled) - Herman, B. E.; Szabó, J.; Bacsa, I.; Wölfling, J.; Schneider, G.; Bálint, M.; Hetényi, C.; Mernyák, E.; Szécsi, M. (J. Enzyme Inhib. Med. Chem., 2016)

(untitled) - Bacsa, I.; Jójárt, R.; Schneider, G.; Wölfling, J.; Maróti, P.; Herman, B. E.; Szécsi, M.; Mernyák, E. (Steroids, 2015)

(untitled) - Bacsa, I.; Jójárt, R.; Wölfling, J.; Schneider, G.; Herman, B. E.; Szécsi, M.; Mernyák, E. (Beilstein J. Org. Chem., 2017)

(untitled) - Bacsa, I.; Herman, B. E.; Jójárt, R.; Herman, K. S.; Wölfling, J.; Schneider, G.; Varga, M.; Tömböly, C.; Lanisnik-Rizner, T.; Szécsi, M.; Mernyák, E. (J. Enzyme Inhib. Med. Chem., 2018)

(untitled) - Möller, G.; Deluca, D.; Gege, C.; Rosinus, A.; Kowalik, D.; Peters, O.; Droescher, P.; Elger, W.; Adamski, J.; Hillisch, A. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Phan, C.-M.; Liu, Y.; Kim, B.-m.; Mostafa, Y.; Taylor, S. D. (Bioorg. Med. Chem., 2011)

(untitled) - Hirao, T.; Masunaga, T.; Ohshiro, Y.; Agawa, T. (Tetrahedron Lett., 1980)

(untitled) - Kegelvich, G.; Jablonkai, E.; Balázs, L. B. (RSC Adv., 2014)

(untitled) - Dziuganowska, Z. A.; Ślepokura, K.; Volle, J.-N.; Virieux, D.; Pirat, J.-L.; Kafarski, P. (J. Org. Chem., 2016)

(untitled) - Keglevich, G.; Henyecz, R.; Mucsi, Z.; Kiss, N. Z. (Adv. Synth. Catal., 2017)

(untitled) - Bacsa, I.; Szemerédi, D.; Wölfling, J.; Schneider, G.; Fekete, L.; Mernyák, E. (Beilstein J. Org. Chem., 2018)

(untitled) - Patik, I.; Székely, V.; Német, O.; Szepesi, Á.; Kucsma, N.; Várady, G.; Szakács, G.; Bakos, É.; Özvegy-Laczka, C. (Sci. Rep., 2018)